2013
DOI: 10.1021/es403667b
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Photooxidation of As(III) through Surface Complexation with Nascent Colloidal Ferric Hydroxide

Abstract: Contamination of water and soils with arsenic, especially inorganic arsenic, has been one of the most important topics in the fields of environmental science and technology. The interactions between iron and arsenic play a very significant role in the environmental behavior and effect of arsenic species. However, the mechanism of As(III) oxidation in the presence of iron has remained unclear because of the complicated speciation of iron and arsenic. Photooxidation of As(III) on nascent colloidal ferric hydroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 47 publications
3
61
0
Order By: Relevance
“…It indicated the important role of visible light in the heterogeneous Fenton process for the degradation of RhB. The quantum yield ( ) was estimated to examine the photodegradation efficiency [39,64], which was found to be (1.66 ± 0.21) × 10 −2 (see Supplementary Material for detail). In order to explore the contribution of photolysis to the removal of RhB, the dye was irradiated by visible light alone, with the adsorption equilibrium concentration of RhB being selected as the initial dye concentration.…”
Section: Visible Light Photo-fenton Catalytic Activity Of Fe-bmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicated the important role of visible light in the heterogeneous Fenton process for the degradation of RhB. The quantum yield ( ) was estimated to examine the photodegradation efficiency [39,64], which was found to be (1.66 ± 0.21) × 10 −2 (see Supplementary Material for detail). In order to explore the contribution of photolysis to the removal of RhB, the dye was irradiated by visible light alone, with the adsorption equilibrium concentration of RhB being selected as the initial dye concentration.…”
Section: Visible Light Photo-fenton Catalytic Activity Of Fe-bmentioning
confidence: 99%
“…Compared to conventional light sources, light-emitting diode (LED) lamps are small in size, robust, environmentally friendly, which have relatively low costs but a longer life span [38]. More importantly, the LED lamps are not calorigenic, and then the reactions can be performed at room temperature without the use of cooling water [39]. Therefore, in this study, natural bentonite clay was used as support to synthesize photo-Fenton catalyst (Fe-supported bentonite, denoted as Fe-B) and LED lamps with a central wavelength of 455 nm were employed as visible light sources.…”
Section: Introductionmentioning
confidence: 99%
“…The competitive reaction for 1 O 2 was also performed in an LED reactor, which was the same as that used in previous work [22]. The UV-C lamps used for photolysis of HBCD mainly have emission at wavelengths between 224 and 254, 266, 276, 281 and 290 nm as shown in Fig.…”
Section: Competitive Reactionmentioning
confidence: 99%
“…HO • reacts with As(III) more rapidly than do HO 2 • or H 2 O 2 and mainly oxidizes As(III) to As(IV) in photochemical systems containing iron oxides and iron hydroxides (Wang et al 2013a, b;Xu et al 2013). The intermediate As(IV) can be easily oxidized to As(V) by either Fe(III), O 2 , or HO • , as shown in reactions (4), (5), and (6), respectively.…”
Section: Responsible Editor: Angeles Blancomentioning
confidence: 99%
“…The intermediate As(IV) can be easily oxidized to As(V) by either Fe(III), O 2 , or HO • , as shown in reactions (4), (5), and (6), respectively. Additionally, Xu et al (2013) reported a novel pathway of As(III) photooxidation on nascent colloidal ferric hydroxide in aqueous solutions. The surface complex formed by reaction of As(III) and ferric hydroxide can undergo ligand-to-metal charge-transfer from As(III) to As(V) under irradiation (Woods et al 1963;Dutta et al 2005).…”
Section: Responsible Editor: Angeles Blancomentioning
confidence: 99%